(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Dragon fruit dye has been prepared and used in the fabrication of DSSC as sensitizer. The properties of dragon fruit dye have been investigated by UV-Vis and FTIR technique. The absorption spectrum shows a peak value of 535 nm. Chemically dragon fruit dye shows present of intermolecular H-bond, conjugate C=O stretching and esters acetates C-O-C stretching vibration, which is due to the component of anthocyanin. On the other hand, the resistivity of TiO2 film on ITO glass before it is used for the fabrication of DSSC is also investigated. The TiO2 sheet resistivity increase from 1 layer = 22.1 Ω cm to 2 layers = 369.6 Ω cm. Finally, the efficiency of assemble DSSC was evaluated and simulated using a custom made technique. The result shows fill factor, Pmax and efficiency during the present of halogen lamp are 0.30, 13 µW, 0.22%, respectively. We have successfully showed that the DSSC using dragon fruit as a dye sensitizer is useful for the preparation of environmental friendly and low-cost DSSC.